The Louisiana Healthy Communities Initiative: A Community-Participatory Model for Obesity Prevention. (29th May 2020) - Greene, Matthew; Stroope, Jessica; Holston, Denise
Abstract: Objectives: Louisiana ranks 4th among US states for adult obesity, and 5th highest for physical inactivity. The Healthy Communities Initiative is a novel effort led by Cooperative Extension (CE) and SNAP-Ed staff in Louisiana to change the policy, systems, and environment (PSE) in target communities to encourage increased physical activity and healthier eating behaviors. The objective of this qualitative study was to identify community members' perceived impacts of the Healthy Communities Initiative on their community according to the Community Capitals Framework using ripple effect mapping. Methods: Local CE staff hold community forums where residents identify and prioritize strategies for PSE changes, then recruit community coalition members to collectively address needs identified at the forum. PSE strategies are different for each community targeted, with short-term impacts most effectively evaluated using qualitative methods. Ripple effect mapping is a community participatory qualitative evaluation method which allows evaluators to capture the effects of innovative interventions. Evaluators facilitate a focus group session in which community members create a map of the multiple impacts of an intervention according to the constructs of the Community Capitals Framework. We held a ripple effect mapping session with 15 participants in one Healthy Communities coalition to evaluate their progress after one year of PSE change work. Results: Community members identified program impacts in each of the constructs of the community capitals framework. Participants most often identified program impacts that were improvements to the community's political capital, such as an improved ability to advocate for change. Participants identified the most impactful outcomes of the program, which included an increased awareness of inequity in the community, increased access to fresh produce for community members, and making connections with agencies and organizations which stretched across organizations' "silos." Conclusions: The Louisiana Healthy Communities Initiative is an innovative strategy to encourage the adoption of PSE changes for obesity prevention. Ripple effect mapping proved to be an effective method for assessing community members' perceptions of program impacts. Funding Sources: SNAP-Ed.